Analisis Strategi Peningkatan Kualitas Produk Bakso dengan Menggunakan Metode Six Sigma Pada Berkah Usaha Bakso Rori - Ardita Dwi Agustin; Ade Momon (Tekinfo: Jurnal Ilmiah Teknik Industri dan Informasi, 2025)
UMKM Berkah Usaha Bakso Rori is a company engaged in the meatball production sector, specializing in packaged meatballs marketed in various markets. This research aims to identify and reduce the frequency of defects by applying the Six Sigma approach, which includes the steps of Define, Measure, Analyze, Improve, and Control, starting with field observations to identify existing problems. Furthermore, this study involves problem formulation, setting research objectives, and gathering relevant information to analyze and reduce defects in the production process. The collected data will be analyzed using statistical tools, such as Pareto charts, P-Charts, and fishbone diagrams, which help identify the main factors causing defects in the meatball products. The research output shows that defects in the meatball products consist of packaging defects and shape defects. The calculation of the Current Level (CL) results in a value of 0.003. Meanwhile, the calculations for the Upper Control Limit (UCL) and Lower Control Limit (LCL) during the first observation show values of 0.008 and 0, indicating uncontrolled variation in the production process. Based on the Failure Mode and Effect Analysis (FMEA), the failure mode of crumbled meatballs has the highest Risk Priority Number (RPN), with a value of 240. This risk is primarily caused by human factors, namely employees rushing during the packaging process. Based on these findings, this research provides recommendations for improvements, including enhanced training for employees, quality control during the packaging process, and a review of packaging procedures to reduce product defects and improve the quality of the meatballs produced.